2023
DOI: 10.1155/2023/6152905
|View full text |Cite
|
Sign up to set email alerts
|

The Autosomal Short Tandem Repeat Polymorphisms Are Potentially Associated with Cardiovascular Disease Predisposition in the Latin American Population: A Mini Review

Ana Karina Zambrano,
Santiago Cadena-Ullauri,
Patricia Guevara-Ramírez
et al.

Abstract: According to the World Health Organization, cardiovascular diseases (CVDs) are the leading cause of death worldwide across nearly all ethnic groups. Inherited cardiac conditions comprise a wide spectrum of diseases that affect the heart, including abnormal structural features and functional impairments. In Latin America, CVDs are the leading cause of death within the region. Factors such as population aging, unhealthy diet, obesity, smoking, and a sedentary lifestyle have increased the risk of CVD. The Latin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(106 reference statements)
0
0
0
Order By: Relevance
“…The World Health Organization (WHO) has identified cardiovascular diseases (CVDs) as the primary cause of death, accounting for more than 17.9 million deaths worldwide across diverse ethnic groups [ 1 ]. In Ecuador, the WHO reported that CVDs accounted for 21% and 20% of total male and female deaths, respectively, in 2014 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) has identified cardiovascular diseases (CVDs) as the primary cause of death, accounting for more than 17.9 million deaths worldwide across diverse ethnic groups [ 1 ]. In Ecuador, the WHO reported that CVDs accounted for 21% and 20% of total male and female deaths, respectively, in 2014 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%